Seroprevalence and epidemiological correlates of Toxoplasma gondii infections among patients referred for hospital-based serological testing in Doha, Qatar - Abu-Madi, Marwan A.; Al-Molawi, Naema; Behnke, Jerzy M. (BioMed Central, 2008)
Background: The city of Doha in Qatar has a high density of feral cats and there is a high risk of toxoplasmosis for the resident human population. No data currently exist for the prevalence of infection with Toxoplasma gondii in the city. Methods: We analysed the serological response to Toxoplasma gondii of 1625 subjects referred for routine hospital based serological tests in Doha, Qatar. Prevalence of current/recent infection was assessed through an enzyme-linked immunosorbent assay (ELISA) for the presence of specific anti-T. gondii IgM antibodies, and previous history of infection through IgG.